Impact of Cardiovascular-Respiratory Parameters on High-Intensity Football Training - Sheng Wang; Hyongjun Choi; Xiaohui Jiang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The efficacy of soccer players is influenced by morphological, functional, and psychological characteristics that define the optimal playing style and game outcomes. It is generally accepted that soccer is a prolonged, high-intensity, intermittent sport where players must sprint repeatedly and frequently throughout a 90-minute match. The average intensity of their exercise is between 80 and 90 percent of their maximum heart rate or anaerobic threshold. This innovative study aims to determine how high-intensity football affects cardiovascular and pulmonary characteristics. The data for this study are collected using a Likert scale from university soccer players. The research revealed that cardiovascular and respiratory parameters significantly influence high-intensity football training. This study is innovative due to its research concept and substantial implications for theory and practice. The prospective directions of this research are also essential for critically advancing the body of knowledge.